KONTROVERSI PENERAPAN HERMENEUTIKA DALAM PENAFSIRAN AL-QUR’AN - Mohamad khoiril Anwar; Abdul Rasyid Ridho (el-'Umdah, 2021)
Hermeneutics its simplest sense is the theory of text interpretation which was originally used to interpret the Bible. The use of the hermeneutic approach, especially in Indonesia, can be traced through existing courses and research results. The presence of hermeneutics has drawn controversy, especially when it is associated with the al-Qur’an. So there are some who disagree with hermeneutics because this hermeneutics is not from Islam so that it cannot be used in interpreting the Qur'an because it is seen from its history that hermeneutics is used to interpret Biebel which is actually different from the al-Qur'an. Although this hermeneutics is not used in interpreting the Qur'an, according to the author's n, it looks more at the goal of an interpretation, which is to make it easier for humans to understand a text.The highest and foremost authority in interpreting the al-Qur’an is only the Prophet Muhammad SAW, so at that time, if the companions had difficulty understanding the Qur'an, they immediately asked the Prophet. Then in the development of the methodology of interpretation, a form of interpretation emerged, namely the form of history (tafsir bi al-ma'tsur) in which the companions received and narrated the interpretation of the Prophet Muhammad SAW through deliberation and tafsir al-ra'y (interpretation through thought or ijtihad).